A Study on the Information Security Management Index through Analysis of EU-GDPR (European Union-General Data Protection Regulation) - Yoon, Jin-Hwan; Shin, Yong-Tae; Kim, Jong-Bae (International Journal of Engineering and Technology, 2019)
The European Commission is committed to ensuring the free movement of personal information between EU Member States and strengthening the protection of the privacy of information by EU Member States through the EU General Regulations 2016/679 (General Data Protection Regulation: 'GDPR'), which entered into force on May 24, 2016, andÂ effect on May 25, 2018, and will have direct application and legal binding power to all EU Member States.Companies that are servicing the EU or preparing for business need to have a good understanding of the GDPR compliance requirements and need to comply with the relevant regulatory requirements.This study compares the legal core requirements between GDPR and domestic law, compares and analyzes the control items of ISMS (Information Security Management System & PIMS: Personal Information Management System) with the requirements of GDPR suggest ways to prepare a response system.Â Â